Study of chronic toxicity of the GB-115 drug formulation - A. V. Sorokina; S. V. Alekseeva; I. A. Miroshkina; V. V. Zabrodina; L. G. Kolik; A. D. Durnev (LLC "Publisher OKI", 2020)
The results of the study of chronic toxicity of the drug formulation of anxiolytic GB-115 are presented. The novel dipeptide in the form of a tablet mass was administered daily orally for 6 months to outbred rats and rabbits of the chinchilla breed at a dose of 1 mg/kg corresponding to the therapeutic and 50 mg/kg exceeding the therapeutic dose by 50 times. Clinical, laboratory and pathohistological studies performed in accordance with the General Protocol demonstrated the absence of toxic effects of the GB-115 drug formulation. The exception was the reversible changes in the coagulation activity in rats and rabbits, which were not associated with the dose of the GB-115 solid dosage from.